THE INFLUENCE OF RAINFALL ON SEDIMENT TRANSPORT BY OVERLAND FLOW OVER AREAS OF NET DEPOSITION - Beuselinck L.; Govers G.; Hairsine P.B.; Sander G.C.; Breynaert M. (My University, 2002)
Overland flow is often only a few millimetres deep. Consequently, the potential for raindrop impact to affect flow hydraulics and sediment transport is high. Furthermore, the relative importance of rainfall impact is highest for shallow low-energy flows on low slopes. In such flows net sediment deposition may occur. Therefore, laboratory experiments were conducted to study sediment deposition in the presence of rainfall over a range of hydraulic conditions. In order to investigate the impact of raindrops on sediment deposition by overland flow, these experimental data were compared to the experimental data collected in the absence of raindrop impact. Comparison of the experimental data shows that raindrop impact retards the flow velocity and has a clear positive effect on sediment delivery. Under rainfall significantly more coarse sediment is transported over areas of net sediment deposition. Subsequently, the experimental results are used to evaluate a multi-class net deposition theory, describing sediment transport and sediment sorting over areas of net deposition in the presence of both raindrop impact and flow-driven processes. The multi-class theory is calibrated using part of the experimental data. Evaluation of the model predictions using the other part of the data shows that the optimised model is able to accurately predict sediment delivery and sediment sorting over areas of net deposition.
Keywords: OVERLAND FLOW; SEDIMENT DEPOSITION; SEDIMENT SORTING; RAINDROP IMPACT